Evaluation of clinical and laboratory findings of children who have had hepatitis a virus infection - Deveci, Uğur; Acar, Ufuk; Salı, Enes (AVES, 2021)
Objective: Hepatitis A virus (HAV) infection is a common disease in the community and can cause significant morbidity and mortality in older ages. This study to investigate and discuss the clinical and laboratory find-ings, treatment and prognosis of children with acute viral hepatitis A in our hospital. Material and Methods: Clinical and laboratory findings of 105 children di-agnosed with acute HAV infection between January 2017 and December 2017 in Şanlıurfa Training and Research Hospital, south-east Turkey, were examined. Results: 54.3% (n= 57) of the patients were males, and mean age was 6.7 ± 3.4 years (range: 1-17 years). 65.7% of the patients were Syrian refugees, and most of the cases were admitted in winter and autumn months. The most common symptoms were jaundice (93.3%), fatigue (76.2%), fever (67.6%), anorexia (66.6%) and abdominal pain (57.1%). Serum AST, ALT, ALP, GGT, total bilirubin and direct bilirubin levels were high in all patients. Hematologic abnormalities and acute liver failure occurred in 53.4% and 3.8% of the cases, respectively. Two patients (1.9%) had gallbladder hy-drops, one patient (0.9%) had reactive arthritis and one patient (0.9%) had autoimmune hepatitis. Overall mortality rate was 0.9%. Conclusion: HAV infection is still an important public health problem in our country. The disease ranges from mild clinical course to complicat-ed cases such as acute liver failure. Improving environmental conditions along with immunization and educating the public on hygiene are very important in disease prevention. © 2021, AVES. All rights reserved.
Hepatit a virüsü enfeksiyonu geçiren çocukların klinik ve laboratuvar bulgularının değerlendirilmesi
Keywords: Acute liver failure; Childhood; Clinical; Hepatitis A virus; Laboratory